Running ABC: Metode latihan untuk optimalisasi kecepatan lari atlet pelajar - Roma, Roma; Bayu, Wahyu Indra; Destriana, Destriana Destriana; Victorian, Ahmad Richard (Universitas Tanjungpura, 2024)
Student athletes often do not have good basic techniques in performing running movements, resulting in the resulting running speed is also not optimal. This study aims to increase the running speed of Lesson athletes with the ABC running method. This research is a quantitative study that uses a quasy experimental research design. This study uses a pre-experimental research design with a one group pretest posttest design. The results of research from 30 samples by collecting 100-meter running speed data on Baturaja Runner Club Student Athletes. Based on the results of data analysis, there is a significant effect of ABC running training on the results of 100-meter running speed in Baturaja Runner Club athletes with a tcount of 5.516 ttable 2.045, a significance value of 0.000 a = 0.05 and with a percentage increase of 34.03%. Based on these data, it can be concluded that there is an average difference between the pretest and posttest training results, which means that the ABC running method has a significant impact in improving the results of running speed in student athletes